Chemical modulators of protein misfolding and neurodegenerative disease - Seneci, Pierfausto, 1960- (Boston : Elsevier/AP, Academic Press is an imprint of Elsevier, 2015)
This book is a neurochemistry-based companion for Protein Misfolding and Neurodegenerative Diseases: Molecular Targets, an Elsevier title by the same author publishing in December 2014. While the first book focuses on biology and molecular targets, this companion book describes how these targets are regulated by small molecules and disease-modifying compounds. The book begins with a brief introduction to how key proteins become dysfunctional, and each subsequent chapter describes major disease mechanisms in Alzheimer's and other tauopathies. Properties and development status of these molecular targets and disease mechanisms are thoroughly described, as are small molecule effectors of autophagy and dis-aggregating agents. Written to provide comprehensive coverage of neurodegenerative disease-modifying compounds Provides discipline-specific chapters that cover medicinal chemistry and clinical applications Provides an overview of more than 200 chemical classes and lead compounds, acting on selected molecular targets that are of relevance to any neurodegenerative disorder Coverage of misfolding diseases, chaperone proteins, ubiquitination and autophagy/oncology makes this book suitable for structural neurochemists, chemists, biologists, non-CNS scientists, and scientists interested in drug discovery.